Leukemic Stem Cell: A Mini-Review on Clinical Perspectives - Barreto, Igor Valentim; Pessoa, Flávia Melo Cunha de Pinho; Machado, Caio Bezerra; Pantoja, Laudreísa da Costa; Ribeiro, Rodrigo Monteiro; Lopes, Germison Silva; Amaral de Moraes, Maria Elisabete; de Moraes Filho, Manoel Odorico; de Souza, Lucas Eduardo Botelho; Burbano, Rommel Mário Rodriguez; Khayat, André Salim; Moreira-Nunes, Caroline Aquino (Frontiers in Oncology, 2022)
Hematopoietic stem cells (HSCs) are known for their ability to proliferate and self-renew, thus being responsible for sustaining the hematopoietic system and residing in the bone marrow (BM). Leukemic stem cells (LSCs) are recognized by their stemness features such as drug resistance, self-renewal, and undifferentiated state. LSCs are also present in BM, being found in only 0.1%, approximately. This makes their identification and even their differentiation difficult since, despite the mutations, they are cells that still have many similarities with HSCs. Although the common characteristics, LSCs are heterogeneous cells and have different phenotypic characteristics, genetic mutations, and metabolic alterations. This whole set of alterations enables the cell to initiate the process of carcinogenesis, in addition to conferring drug resistance and providing relapses. The study of LSCs has been evolving and its application can help patients, where through its count as a biomarker, it can indicate a prognostic factor and reveal treatment results. The selection of a target to LSC therapy is fundamental. Ideally, the target chosen should be highly expressed by LSCs, highly selective, absence of expression on other cells, in particular HSC, and preferentially expressed by high numbers of patients. In view of the large number of similarities between LSCs and HSCs, it is not surprising that current treatment approaches are limited. In this mini review we seek to describe the immunophenotypic characteristics and mechanisms of resistance presented by LSCs, also approaching possible alternatives for the treatment of patients.